Button switch circuit based on piezoresistive effect - DI BIN (2018)
The utility model discloses a button switch circuit based on piezoresistive effect, the button switch circuit is including integrated piezoelectric transduction IC, integrated signal processing IC, MCU processing module and output control module, the utility model discloses utilize piezoresistive effect with the accurate change that turns into the signal of telecommunication of pressure variation,measure the pressure value that this signal of telecommunication can the accurate button switch of obtaining be pressed, then control button switch through the change of judgement pressure value, abundant application module circuit integrate the design, reduced size reduces the consumption, reinforcing product anti -interference ability, broken through traditional button switch's the restrictionof using, through obtaining accurate button pressure value, can realize button switch's digitally controlled, be convenient for promote in the industry and use. 本实用新型公开了种基于压阻效应的按钮开关电路，所述按钮开关电路包括集成压电转换IC、集成信号处理IC、MCU处理模块和输出控制模块